Observations of Diurnal to Weekly Variations of Monoterpene-Dominated Fluxes of Volatile Organic Compounds from Mediterranean Forests: Implications for Regional Modeling - Fares, Silvano; Schnitzhofer, Ralf; Jiang, Xiaoyan; Guenther, Alex; Hansel, Armin; Loreto, Francesco (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2013)
The Estate of Castelporziano (Rome, Italy) hosts many ecosystems representative of Mediterranean vegetation, especially holm oak and pine forests and dune vegetation. In this work, basal emission factors (BEFs) of biogenic volatile organic compounds (BVOCs) obtained by Eddy Covariance in a field campaign using a proton transfer reaction-time-of-flight-mass spectrometer (PTR-TOF-MS) were compared to BEFs reported in previous studies that could not measure fluxes in real-time. Globally, broadleaf forests are dominated by isoprene emissions, but these Mediterranean ecosystems are dominated by strong monoterpene emitters, as shown by the new BEFs. The original and new BEFs were used to parametrize the model of emissions of gases and aerosols from nature (MEGAN v2.1), and model outputs were compared with measured fluxes. Results showed good agreement between modeled and measured fluxes when a model was used to predict radiative transfer and energy balance across the canopy. We then evaluated whether changes in BVOC emissions can affect the chemistry of the atmosphere and climate at a regional level. MEGAN was run together with the land surface model (community land model, CLM v4.0) of the community earth system model (CESM v1.0). Results highlighted that tropospheric ozone concentration and air temperature predicted from the model are sensitive to the magnitude of BVOC emissions, thus demonstrating the importance of adopting the proper BEF values for model parametrization.
The following values have no corresponding Zotero field: pub-location: 1155 16TH ST, NW, WASHINGTON, DC 20036 USA publisher: AMER CHEMICAL SOC
Keywords: Emissions; GLOBAL-MODEL; Ozone; PROTON-TRANSFER REACTION; PTR-TOF; QUERCUS-ILEX; REACTION MASS-SPECTROMETRY

Seasonal variations in terpene emission factors of dominant species in four ecosystems in NE Spain - Llusia, Joan; Penuelas, Josep; Guenther, Alex; Rapparini, Francesca (Atmospheric Environment, 2013)
We studied the daily patterns in the rates of foliar terpene emissions by four typical species from the Mediterranean region in two days of early spring and two days of summer in 4 localities of increasing biomass cover in Northern Spain. The species studied were Thymelaea tinctoria (in Monegros), Quercus coccifera (in Garraf), Quercus ilex (in Prades) and Fagus sylvatica (in Montseny). Of the total 43 VOCs detected, 23 were monoterpenes, 5 sesquiterpenes and 15 were not terpenes. Sesquiterpenes were the main terpenes emitted from T. tinctoria. Total VOC emission rates were on average about 15 times higher in summer than in early spring. The maximum rates of emission were recorded around midday. Emissions nearly stopped in the dark. No significant differences were found for nocturnal total terpene emission rates between places and seasons. The seasonal variations in the rate of terpene emissions and in their chemical composition can be explained mainly by dramatic changes in emission factors (emission capacity) associated in some cases, such as for beech trees, with very different foliar ontogenical characteristics between spring and summer. The results show that temperature and light-standardised emission rates were on average about 15 times higher in summer than in early spring, which, corroborating other works, calls to attention when applying the same emission factor in modelling throughout the different seasons of the year.
Keywords: climatic gradient; Emission rates; Mediterranean ecosystems; Seasonality; terpenes

Seasonal variations in terpene emission factors of dominant species in four ecosystems in NE Spain - Llusia, Joan; Penuelas, Josep; Guenther, Alex; Rapparini, Francesca (Atmospheric Environment, 2013)
We studied the daily patterns in the rates of foliar terpene emissions by four typical species from the Mediterranean region in two days of early spring and two days of summer in 4 localities of increasing biomass cover in Northern Spain. The species studied were Thymelaea tinctoria (in Monegros), Quercus coccifera (in Garraf), Quercus ilex (in Prades) and Fagus sylvatica (in Montseny). Of the total 43 VOCs detected, 23 were monoterpenes, 5 sesquiterpenes and 15 were not terpenes. Sesquiterpenes were the main terpenes emitted from T. tinctoria. Total VOC emission rates were on average about 15 times higher in summer than in early spring. The maximum rates of emission were recorded around midday. Emissions nearly stopped in the dark. No significant differences were found for nocturnal total terpene emission rates between places and seasons. The seasonal variations in the rate of terpene emissions and in their chemical composition can be explained mainly by dramatic changes in emission factors (emission capacity) associated in some cases, such as for beech trees, with very different foliar ontogenical characteristics between spring and summer. The results show that temperature and light-standardised emission rates were on average about 15 times higher in summer than in early spring, which, corroborating other works, calls to attention when applying the same emission factor in modelling throughout the different seasons of the year.
Keywords: climatic gradient; Emission rates; Mediterranean ecosystems; Seasonality; terpenes